[Two images] [Top image:] J.P. Andrews Bank [Bottom image:] House of Reverend J.N. Wilson (1893)
Above: The J.P. Anderson Bank at 998 Monterey Street in San Luis Obispo, CA constructed in 1893. Below: Two women, a child, and a dog in front of the house of Reverend J.N. Wilson in San Luis Obispo, CA. Exact location and date unknown for bottom photo.